Achieving Accurate In-Text Citations with EndNote in Academic Writing - Sharma, Uma Nath (Siddhajyoti Interdisciplinary Journal, 2024)
EndNote, alongside other citation management software programs like RefWorks, Mendeley, and Zotero, functions as a crucial instrument for archiving, structuring, accessing, and referencing sources in scholarly composition. This study delves into my personal experience of refining EndNote’s default in-text citations across various reference types, for achieving accurate in-text citations adhering to the American Psychological Association (APA) style. To do so, I compiled my personal, albeit disjointed, experiences with refining the default in-text citation format sourced from the EndNote library. The findings are presented and discussed in a thematic manner, focusing on the in-text citation types and how they can be effectively managed within Microsoft (MS) Word documents. The findings ultimately affirm that EndNote’s default in-text citations can be tailored to accurately cite a broader spectrum of citation types. This implies that judicious use of EndNote facilitates precise and systematic citations, with minimal manual adjustments. This consequently streamlines and accelerates the entirety of the course of academic writing.